2005
DOI: 10.1111/j.1463-1318.2005.00769.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of long‐term quality of life after laparoscopic and open surgery for Crohn's disease

Abstract: QOL is significantly reduced in patients with CD at long-term follow-up after both laparoscopic and open surgery. Recurrence is the only factor adversely affecting QOL of CD patients in remission irrespective of the operative technique applied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 29 publications
3
42
0
1
Order By: Relevance
“…1). Of 27 publications that were considered potentially relevant[2,3,4, 8, 9,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33], 13 were subsequently excluded due to the reasons given in figure 1[14,18,19,20,21,24,25,26,27, 29, 30, 33]. Fourteen studies published between 1995 and 2006 met the inclusion criteria [2,3,4, 8, 9, 12, 13, 15, 17, 22, 23, 28, 31, 32].…”
Section: Resultsmentioning
confidence: 99%
“…1). Of 27 publications that were considered potentially relevant[2,3,4, 8, 9,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33], 13 were subsequently excluded due to the reasons given in figure 1[14,18,19,20,21,24,25,26,27, 29, 30, 33]. Fourteen studies published between 1995 and 2006 met the inclusion criteria [2,3,4, 8, 9, 12, 13, 15, 17, 22, 23, 28, 31, 32].…”
Section: Resultsmentioning
confidence: 99%
“…Whether rapid recovery from the minimally invasive approach results in restoration of QOL to preoperative levels soon after surgery has not previously been investigated. Laparoscopic colorectal resection has been reported to be superior to open surgery with regard to minor complications and improved QOL during the first postoperative month [11], whereas QOL is similar in the long term [12,13]. In contrast, very little difference was found between the two approaches at 2-week and 3-month follow-up, with most instruments showing worse QOL at 2 weeks in both cases, with a return to baseline at 3 months [1].…”
Section: Introductionmentioning
confidence: 63%
“…As a result, improvement in QOL is expected after LCR in the short term. Some studies have shown that when compared to open colectomy, LCR is superior with regard to minor complications, lower analgesic requirements [3][4][5][6][7][8][9][10], and improved QOL during the first postoperative month [2,11], whereas QOL is similar in the long term [12,13]. QOL has also been reported to improve after esophageal surgery, cholecystectomy, and splenectomy 6 weeks after both open and laparoscopic surgery [15].…”
Section: Discussionmentioning
confidence: 98%
“…Improved cosmesis may be particularly important because patients with Crohn's disease tend to be young. In this regard, it has been suggested that the predominant factor determining quality of life in the long run is disease recurrence and not the surgical approach [15]. An advantage of a laparoscopic procedure is lower overall costs compared with open surgery, as demonstrated Maartense et al [10] and Young-Fadok et al [16].…”
Section: Discussionmentioning
confidence: 94%